PENGARUH PENGGUNAAN ABU DAUN BAMBU SEBAGAI PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN BETON SEBAGAI PENDUKUNG BAHAN AJAR MATA KULIAH TEKNOLOGI BETON - Aji Firmansyah (Menara: Jurnal Teknik Sipil, 2022)
The purpose of this study was to determine the compressive strength of concrete using bamboo leaf ash as a partial replacement of cement with a target compressive strength of 25 MPa at the age of 28 days with the use of water cement factor (FAS) 0,5 and variation percentage levels of bamboo leaf ash that be used are 0%, 5%, 7%, 9%, and 11% of the total weight of cement. The The amboo leaf ash used comes from Andong bamboo species. In this study use the experimental method with cylindrical specimens with a diameter of 15 cm and a height of 30 cm as many as 3 samples in each percentage level of bamboo leaf ash. Concrete mix design refers to SNI 03-2834-2000. The results obtained indicate that bamboo leaf ash can increase the compressive strength of concrete when compared to the control concrete in this study even though the increase is not too large. The compressive strength of concrete at the age of 28 days at 0%, 5%, 7%, 9%, and 11% percentages levels of bamboo leaf ash were 16,448 MPa ; 18,768 MPa ; 18,297 MPa ; 14,958 MPa ; dan 12,827 MPa.